Assessment of the pharmacokinetic profile of novel s-triazine derivatives and their potential use in treatment of Alzheimer's disease - Trifunovic, J.; Borcic, V.; Vukmirovic, S.; Mikov, Momir (Elsevier, 2017)
© 2016 Elsevier Inc. Aims The current treatment of Alzheimer's disease is purely symptomatic. Scientists are looking for new treatment options which could alter the course of the disease and improve the quality of life in patients with Alzheimer's disease. In this paper 14 novel s-triazine molecules have been evaluated for their lipophilicity. In addition docking study was carried out to evaluate acetylcholinesterase activity of these compounds. Main methods Lipophilicity was evaluated by RP HPTLC using 5 different mobile phases and obtained results were used in calculations of pharmacokinetic parameters - logBB, Ka and Pej. Multiple linear regression analysis was refined, taking account of molecular polarity (total polar surface area, TPSA) and molecular weight (Mw) descriptors. Appropriate QSAR models were developed. Docking studies were carried out using the Vina docking. Key findings Five out of fourteen compounds evaluated [5-10] are selected as the most promising compounds with satisfactory pharmacokinetic properties and good docking scores. Significance Compound 10 possesses the best combination of favourable pharmacokinetic characteristics (brain penetration, intestinal absorption) and capacity for acetylcholinesterase inhibition. Consequently this molecule should be further evaluated for potential therapeutic use in Alzheimer's disease.